Kajian Manajemen Mutu Usaha Kecil Menengah Sepatu di PD. Anugerah Hero - Ciomas - - Susviarto; - Suryahadi; Darwin Kadarisman (Institut Pertanian Bogor, 2012)
Study of Shoes Small Middle Enterprises (SME) Quality Management is held through case study in PD. Anugerah Hero Ciomas Kabupaten Bogor. This study is intend to: (a) knowing about applied level of quality management system in PD. Anugerah Hero, (b) knowing activities done by PD. Anugerah Hero to guarantee it’s product quality, (c) evaluating product quality performance, (d) analyzing how quality cost performance in PD. Anugerah Hero. Determining quality management system practices held by matching quality attempt applied to characteristic quality management system as conducted by Muhandri and Kadarisman. Identification of quality activity held according the Juran Trilogy. Evaluating quality performance held for number of defect product, number of reject/return product, Finishing time late and quality cost analysis. Result of study indicating that the most fit quality management system applied if compared to characteristic of quality management system applied according to Muhandri and Kadarisman is Foreman Quality Control. The activities of quality management held is including; knowing the needs and consumer terms, and designing process and instrument for shoes making for quality planning aspect. The quality management aspect is by compiling standard and specification, using model, mold and pattern and also doing sortation qualitatively by visual inspection. The quality improving aspect is only for doing benchmarking in relatively large shoes industry and duplicating a new model from “mall”, books and magazine. The number of products rejected, especially by abroad customer is ranged between 11,1% – 17,7% by average 15,9 of the number of order. Slowness of finishing time due to the order is on average of 3,8 days or 7,0% compared to order time. The number of order late is about 50%. The quality cost identified is only external failed cost for down grading, is that, about Rp50.415.000 for 11 order in 2007, quality cost index due to the selling omzet is about 2,37%